2019
DOI: 10.1609/aimag.v40i4.4813
|View full text |Cite
|
Sign up to set email alerts
|

Methods of AI for Multimodal Sensing and Action for Complex Situations

Abstract: Artificial intelligence (AI) seeks to emulate human reasoning, but is still far from achieving such results for actionable sensing in complex situations. Instead of emulating human situation understanding, machines can amplify intelligence by accessing large amounts of data, filtering unimportant information, computing relevant context, and prioritizing results (for example, answers to human queries) to provide human–machine shared context. Intelligence support can come from many contextual sources that augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Researchers of this category agree on the stages of input-process-output, with related definitions on data being at rest, in collection, in transition, in motion, or in use. Parallel to this, respective applications increase in ability from purely statistical Baryannis et al (2019a) and Blasch et al (2019) Special applications provided by the sample Business Research AI, which some researchers do not even classify as AI (Baryannis et al 2019a), to human-machine AI (Blasch et al 2019), supporting the framework in Sect. 2.1.2.…”
Section: Categorization Of Ai Applicationsmentioning
confidence: 62%
See 4 more Smart Citations
“…Researchers of this category agree on the stages of input-process-output, with related definitions on data being at rest, in collection, in transition, in motion, or in use. Parallel to this, respective applications increase in ability from purely statistical Baryannis et al (2019a) and Blasch et al (2019) Special applications provided by the sample Business Research AI, which some researchers do not even classify as AI (Baryannis et al 2019a), to human-machine AI (Blasch et al 2019), supporting the framework in Sect. 2.1.2.…”
Section: Categorization Of Ai Applicationsmentioning
confidence: 62%
“…Scholars argue that determining which application to use depends on the type, quantity, and quality of data available, resulting in various necessities to handle the data, such as classification, clustering, or detection of connections (see Table 3). Moreover, as several applications can be used for both top-down and bottom-up approaches (Flath and Stein 2018;Mühlroth and Grottke 2018;Baryannis et al 2019a, b;Blasch et al 2019), the purpose for which the specific application should be used is identified as an additional influence (Blasch et al 2019).…”
Section: Categorization Of Ai Applicationsmentioning
confidence: 99%
See 3 more Smart Citations